Naboth's vineyard: theological lessons for the South African land issue - K. T. Resane (Acta Theologica)
This article is an appeal to South African political and ecclesiastical leaders to form a synergy in order to redress the land issue in the post-apartheid era. It surveys the historical development of land dispossession through various initiatives as a prima for national conflicts in Africa. From the Berlin Conference (1884) to 1990, when the apartheid government relocated millions of Black people to some Bantustans known as homelands, or newly created townships, the land conflicts continued. The dispossession stripped the masses of their dignity, integrity, and respect. The story of Naboth’s vineyard (1 Kgs. 21) is used as a theological framework to redress the land issue. The narrative is expounded to compare the African land perspectives with those of eighth-century Israel. There is an appeal for the ecclesiastical formations to form a synergy with the political stakeholders in addressing this matter.